1981
DOI: 10.1111/j.1399-0004.1981.tb00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability and the biochemical genetics of erythrocyte catechol‐O‐methyltransferase and plasma dopamine‐β‐hydroxylase

Abstract: The levels of activity of human erythrocyte (RBC) catechol‐O‐methyl‐transferase (COMT) and human plasma dopamine‐β‐hydroxylase (DBH) are inherited in a monogenic fashion. The COMT in erythrocytes of subjects homozygous for the allele for low basal enzyme activity, COMTL, is more thermolabile than that in the erythrocytes of subjects with genetically high basal enzyme activity. This observation suggests that the locus COMT may represent the structural gene for COMT in man. Wide individual variations in the ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…methionine). This polymorphism has been shown to substantially aVect COMT enzyme activity, such that homozygosity for the valine allele shows 3-4 times greater activity than homozygosity for the methionine allele (Lotta et al 1995;Scanlon et al 1979;Weinshilboum and Dunnette 1981). Despite the potential relevance of this functional polymorphism to ADHD and an initial small study suggesting that the valine allele of this polymorphism was associated with increased risk for ADHD (Eisenberg et al 1999), the majority of studies have reported negative results (Barr et al 1999;Hawi et al 2000b;Payton et al 2001).…”
Section: Catechol-o-methyl-transferase (Comt)mentioning
confidence: 88%
“…methionine). This polymorphism has been shown to substantially aVect COMT enzyme activity, such that homozygosity for the valine allele shows 3-4 times greater activity than homozygosity for the methionine allele (Lotta et al 1995;Scanlon et al 1979;Weinshilboum and Dunnette 1981). Despite the potential relevance of this functional polymorphism to ADHD and an initial small study suggesting that the valine allele of this polymorphism was associated with increased risk for ADHD (Eisenberg et al 1999), the majority of studies have reported negative results (Barr et al 1999;Hawi et al 2000b;Payton et al 2001).…”
Section: Catechol-o-methyl-transferase (Comt)mentioning
confidence: 88%
“…COMT enzyme activity is genetically polymorphic with a trimodal distribution: high activity for the Val/Val genotype, intermediate activity for the Val/Met genotype, and low activity for the Met/Met genotype. The Met/Met genotype has a 3-to 4-fold lower enzyme activity than the Val/Val genotype [13,16] . This single nucleotide polymorphism is widely referred to as the 158Val/Met polymorphism [17] .…”
Section: Introductionmentioning
confidence: 99%
“…COMT is encoded by a single gene localized on chromosome 22q11.1eq11.2. COMT activity is influenced by a common polymorphism, G158A, which causes substantial variations in enzymatic activity [13] . This polymorphism results in a valine (Val) to methionine (Met) substitution at codon 158 of the membrane-bound form of COMT, which corresponds to codon 108 of the soluble form of COMT [14,15] .…”
Section: Introductionmentioning
confidence: 99%
“…Grossman et al (1992) and Goodman et al (2002) later found that the Val108 and Met108 variations of the human COMT correlated with the phenotypes of high and low levels of COMT catalytic activity, respectively. However, a more detailed analysis of the catalytic activity of these two forms of COMT revealed a similar catalytic property, although the Met108 variant was more thermolabile (37°C), which could be stabilized by AdoMet binding (Weinshilboum and Dunnette, 1981). Studies have also shown that there was a significant correlation between the COMT heated/control ratios and the levels of enzyme activity in the lysates prepared from hepatic tissue and red blood cells.…”
Section: Discussionmentioning
confidence: 92%
“…Human cytosolic COMT is a polymorphic enzyme. Earlier studies with human liver and red blood cells have shown that the low-activity form of the COMT is slightly more sensitive to heat inactivation than its high-activity form (Scanlon et al, 1979;Weinshilboum and Dunnette, 1981). Using eight representative human placenta samples, we determined in the present study their sensitivity to inhibition by gradually increasing the preincubation temperatures from 30 to 50°C (Fig.…”
Section: Zhu Et Almentioning
confidence: 99%